Fuzzy Logic Control of an Induction Generator as an Electrical Brake - Hosseinzadeh, N.; Seyoum, D.; Wolfs, Peter (Spotted Cow Press, 2007)
Fuzzy logic systems (FLS) have been designed to control a self-excited induction generator (SEIG), which is used as a brake. This electrical brake has been designed for the sugar cane industry in Queensland, Australia, which uses brake vans coupled to the end of cane trains to produce a given braking torque. The brake would be suitable for similar applications of electrical brakes in electrically driven machines such as electrical vehicles. This project was established to investigate electrical braking as an alternative to existing mechanical systems. Three fuzzy logic controllers have been designed to control the output retarding torque produced by an induction machine. One of these controllers adjusts the value of a shunt capacitance to maintain the excitation required for the generating operation. The other two adjust the duty cycle of a PWM converter, which drives the load of the induction machine. The duty cycle is adjusted in such a way to keep the retarding torque, produced by the machine, fixed at a given value.